Tissue Kallikrein Alleviates Cerebral Ischemia-Reperfusion Injury by Activating the B2R-ERK1/2-CREB-Bcl-2 Signaling Pathway in Diabetic Rats. (30th June 2016) - Shi, Ruifeng; Yuan, Kunxiong; Hu, Bin; Sang, Hongfei; Zhou, Lizhi; Xie, Yi; Xu, Lili; Cao, Qinqin; Chen, Xin; Zhao, Lingling; Xiong, Yunyun; Xu, Gelin; et al.
Abstract : Diabetes mellitus (DM) substantially increases the risk of ischemic stroke and reduces the tolerance to ischemic insults. Tissue kallikrein (TK) has been demonstrated to protect neurons from ischemia/reperfusion (I/R) injury in orthoglycemic model by activating the bradykinin B2 receptor (B2R). Considering the differential effects of B2R or bradykinin B1 receptor (B1R) on cardioprotection and neuroprotection in I/R with or without diabetes, this study was designed to investigate the role of TK during cerebral I/R injury in streptozotocin-induced diabetic rats. Intravenous injection of TK inhibited apoptosis in neurons, alleviated edema and inflammatory reactions after focal cerebral I/R, significantly reduced the infarct volume, and improved functional recovery. These beneficial effects were accompanied by activation of the extracellular signal-regulated kinase 1/2 (ERK1/2), cAMP response element-binding (CREB), and Bcl-2 signal proteins. Inhibition of the B2R or ERK1/2 pathway abated the effects of TK, whereas an antagonist of B1R enhanced the effects. These findings reveal that the neuroprotective effect of TK against cerebral I/R injury in streptozotocin-induced diabetic rats mainly involves the enhancement of B2R and ERK1/2-CREB-Bcl-2 signaling pathway activity.